Ultrastructural studies on different host-tospovirus combinations - and R.A. SINGH, I.D. GARG, V. HEGDE, S.M. PAUL KHURANA (Indian Phytopathology, 2002)
Ultrastructural studies of tospovirus infected cells of tomato, garden nasturtium (Tropaeolum majus) (Shimla isolates), potato and wild amaranth (Amaranthus blitum) (Gwalior isolates) were undertaken to ascertain if sub-cellular changes induced by these isolates were host specific. Virus was found to be distributed in all the tissues except xylem vessels in tomato and T. majus but confined to the cortical zone of stems in the potato and A. blitum. Tomato and T. majus cells showed in the cytoplasm the occurrence of viroplasm, tubules (T), double-envelope virus-like particles (De) and clusters of mature virus particles enclosed in rough endoplasmic reticulum (Rer) cisternae and paired parallel membranes (Pp). The plasmodesmata (Pd) became pore-likeonly in tomato. Infected cells of potato showed abundance of Rer associated with virus-like particles, while mostly isolated virions were enclosed in smooth endoplasmic reticulum (Ser) and rarely clusters of virions in Rer. Virions occurred mostly as clusters in A. blitum. Neither Pp nor T were observed in potato and A. blitum. Chloroplasts showed peripheral vesicles only in case of A. blitum.